Estradiol Inhibits ER Stress-Induced Apoptosis in Chondrocytes and Contributes to a Reduced Osteoarthritic Cartilage Degeneration in Female Mice - Dreier, Rita; Ising, Thomas; Ramroth, Markus; Rellmann, Yvonne (Frontiers in Cell and Developmental Biology, 2022)
Gender differences are a common finding in osteoarthritis (OA). This may result from a differential response of males and females to endoplasmic reticulum (ER) stress in articular chondrocytes. We have previously described that ER stress in cartilage-specific ERp57 KO mice (ERp57 cKO) favors the development of knee OA, since this stress condition cannot be adequately compensated in articular chondrocytes with increasing age leading to the induction of apoptotic cell death and subsequent cartilage degeneration. The aim of this study was to enlighten gender-specific differences in ER stress, apoptosis, and OA development in ERp57 cKO mice. The analyses were extended by in vitro studies on the influence of estradiol in CRISPR/Cas9-generated C28/I2 ERp57 knock out (KO) and WT cells. ER stress was evaluated by immunofluorescence analysis of the ER stress markers calnexin (Cnx) and binding-immunoglobulin protein (BiP), also referred to as glucose-regulating protein 78 (GRP78) in vivo and in vitro. Apoptotic cell death was investigated by a commercially available cell death detection ELISA and TUNEL assay. OA development in mice was analyzed by toluidine blue staining of paraffin-embedded knee cartilage sections and quantified by OARSI-Scoring. Cell culture studies exhibited a reduction of ER stress and ER stress-induced apoptosis in C28/I2 cells in presence of physiological estradiol concentrations. This is consistent with a slower increase in age-related ER stress and a reduced number of apoptotic chondrocytes in female mice compared to male littermates contributing to a reduced osteoarthritic cartilage degeneration in female mice. Taken together, this study demonstrates that the female sex hormone estradiol can reduce ER stress and ER stress-induced apoptosis in articular chondrocytes, thus minimizing critical events favoring osteoarthritic cartilage degeneration. Therefore, the inhibition of ER stress through a modulation of effects induced by female sex hormones appears to be attractive for OA therapy.